Good Corporate Governance Modeling on Opportunistic Behavior - Related Party Transaction - Lia Ramadhani Fatchan; Trisnawati, *Rina; Erma Setiawati (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study aims to examine the role of good corporate governance in influencing the relationship between family ownership, institutional ownership, and political connections with related party transactions (RPT). The research method uses a quantitative approach with secondary data. Samples using purposive sampling techniques were obtained from 36 mining companies listed on the Indonesia Stock Exchange in the 2017-2022 period. From this sampling technique, after removing incomplete data and outliers, 211 observable data were obtained. Data analysis used moderated regression analysis. The results of the study indicate that good corporate governance is able to moderate the relationship between institutional ownership and political connections with RPT but is unable to moderate between family ownership and RPT. The practical implications of this study can be used as a consideration for the government to make regulations so that the implementation of good corporate governance is more effective in companies whose shares are majority owned by families